Basic principles and substantiation of medical and psychological correction of adaptation disorders in students - Khaustov, M. M. (Journal of Education, Health and Sport, 2018)
The purpose of this work is to identify and develop a system of measures for psychotherapeutic correction on the basis of identification and comprehensive evaluation of clinical and psychological manifestations and mechanisms of formation of maladaptive states in medical students.In order to achieve this aim, in compliance with the principles of bioethics and deontology, 412 students of the 2-5 academic years of the Kharkiv National Medical University, of both sexes, at the age of 17-22 years, were examined.All the surveyed people were divided into three groups: Group 1 included 215 students-inhabitants of the Eastern Ukraine; Group 2 consisted of 87 students-residents of Luhansk and Donetsk regions, who entered the study at the KhNMU before the ATO; Group 3 consisted of 110 students-migrants from the ATO zone.As the results of the study indicated, students- migrants have a higher level of adaptation disorders, compared with the students of the first and second groups. It was established that the structure of adaptation disorders is represented by depressive, neurasthenic, anxious and dissociative syndrome complexes.Prognostically significant elements in the formation of adaptation disorders are excitability and imbalance, proneness to conflicts in relationships, disturbing confidence, disorganization of behavior, failure to self-regulation, inability to successfully overcome stressful situations, act in conditions of uncertainty, rigidity, and focusing on traumatic and negative feelings.In order to correct the disorders of adaptation in medical students, we developed a system of medical and psychological support, which included individualized use of psychotherapeutic and psycho-educational influences. As a feedback of the psychotherapeutic correction, a positive dynamic of the psychological state was noted: rapid reduction of anxiety and depressive symptoms, reduction of the level of neuro-psychic tension, increase of students' psychophysical activity, positive change of coping strategy.